ESTUDO DA EXPRESSÃO DE GENES RELACIONADOS À FUNÇÃO DO EIXO HIPOTALÂMICO-HIPOFISÁRIO-TIREOIDEANO APÓS A EXPOSIÇÃO PRÉ-PÚBERE A NANOPARTÍCULAS DE PRATA (AGNPS), UM POTENCIAL DESREGULADOR ENDÓCRINO QUÍMICO - Oliveira, Isabela Medeiros de (2020)
Silver nanoparticles (AgNPs) have potent antimicrobial activity and are incorporated into a variety of products, raising concern about its potential risks and impacts on human health and the environment. The developmental period is highly dependent on thyroid hormones and puberty is a sensitive period in which changes in the hormonal environment can have permanent effects. Thus, the present study aimed to evaluate the effect of exposure, during the puberty, to low doses of AgNP on the hypothalamic-pituitary-thyroid axis (HPT) and thyroid function. Wistar rats were exposed to 0; 1.875; 3.75; 7.5 or 15 μg of AgNP/kg orally from the postnatal 23 day (PND23) to PND60, when they were euthanized and the hypothalamus, pituitary, thyroid, heart, liver and blood were collected. Reverse Transcription followed by quantitative real-time PCR (RT-qPCR) evaluated the mRNA expression of thyroid hormone responsive genes. The following genes were evaluated: thyrotropin releasing hormone (Trh), monocarboxylate transporter 8 (Mct-8), iodothyronine deiodinase type 1, 2 and 3 (Dio1, Dio2 and Dio3), thyroid hormone receptor alpha 1 and 2 (Thra1 and Thra2), thyroid hormone receptor beta 2 (Thrb2), thyrotropin releasing hormone receptor (Trhr), thyroid stimulating hormone beta (Tshb), thyroid stimulating hormone receptor (Tshr), sodium/iodide simulator (Nis), pendrin (Pds), thyroperoxidase (Tpo). The ribosomal protein L19 (Rpl19) was used as internal control. Quantitative proteomics analysis of the thyroid gland was performed by mass spectrometry and serum concentrations of triiodothyronine (T3) and thyroid stimulating hormone (TSH) were measured by chemiluminescence. In the stimulatory events of the HPT axis was observed an increase in the expression of Trh mRNA and in serum T3 concentration. In negative feedback, there was reduction in Dio2 mRNA expression and increase in Thra1, Thra2 and Thrb2 transcript contents in hypothalamus. In the pituitary, the expression of Mct-8 mRNA and Dio2 mRNA decreased. In peripheral T3-target tissues, Mct-8 mRNA expression was decreased while Dio3 mRNA was increased in the heart and liver and Thrb2 mRNA content only in the liver. The quantitative proteomic profile of the thyroid gland indicated reduction in cytoskeleton proteins (Cap1, Cav1, Lasp1, Marcks and Tpm4), reduction in the profile of chaperones (Hsp90aa1, Hsp90ab1, Hspa8, Hspa9, P4hb) and proteins that participate in the N-glycosylation process (Ddost, Rpn1 and Rpn2). These results demonstrate that exposure to low doses of AgNPs, during the puberty development window, affects the regulation of the HPT axis with consequences on thyroid gland physiology and on target tissues to thyroid hormone actions.